Air‐sea disequilibrium of carbon dioxide enhances the biological carbon sequestration in the Southern Ocean. Issue 4 (19th November 2013) - Ito, Takamitsu; Follows, Michael J.
<x xml:space="preserve">Abstract</x> [1] Sinking and subduction of organic material removes carbon from the surface ocean and stores it in inorganic form after remineralization. The wind‐driven upwelling of deep waters, notably in the Southern Ocean, counteracts the biological carbon sequestration by returning excess carbon from the abyss, potentially releasing it back to the atmosphere. Numerical models have shown that significant fraction of the excess carbon in the Antarctic Surface Water is not degassed to the atmosphere but reenters into the deep ocean due to the incomplete air‐sea equilibration, effectively increasing the efficiency of biological carbon storage in the deep ocean. We develop a simple theory to consider the controls on this effect. The theory predicts a strong coupling between biological carbon sequestration and air‐sea disequilibrium expressed as a linear relationship between the biological carbon pump and the degree of supersaturation in the deep ocean. Sensitivity experiments with a three‐dimensional ocean biogeochemistry model support this prediction and demonstrate that the disequilibrium pump almost doubles the efficiency of biological carbon sequestration, relative to the effect of nutrient utilization.